The Adventure of Geography in Social Studies: A Study on Change - B. Ünal İbret; Onur Yılmaz (Anadolu Üniversitesi Eğitim Fakültesi dergisi)
Geography is one of the important building blocks of the social studies course. For this reason, it is necessary to follow the geography discipline, to renew it with up-to-date information, and to ensure its sustainability in the content of the social studies course. This research aims to be understood how geography, one of the important disciplines of social studies, has changed in secondary school social studies textbooks in the historical process. In the research was carried out document analysis, one of the qualitative research methods. Six textbooks prepared according to the social studies curriculum adopted in 2005 and 2018 were examined. Content analysis was utilized in the data analysis process of the research. As a result of the research, it was observed that the geography topics were reduced in terms of quantity in the period between 2005 and 2022, and the current concepts given in the 2018 curriculum were not reflected in the textbooks.